Labouring Poor in Early Modern Sweden?: Crofters and Lodgers in Västmanland in the 17th Century. Issue 4 (8th August 2019) - Lindström, Jonas
Abstract : We know very little about the unlanded population (obesuttna) in Sweden before 1750. Still, knowledge of this group is vital not only to our understanding of the proletarianization process, but also to the understanding of rural Sweden before the changes of the 18th and 19th centuries. This article takes a step towards filling this gap. Tax registers and church records from 17th-century Västmanland shows substantial proportions of unlanded people, i.e. crofters, cottagers, soldiers, artisans, and lodgers, around 1640 and 1690. The age structure of this group, which can be studied for the latter part of the period, shows that it mostly consisted of people in working age. In conclusion, the article argues that there was a significant group of smallholders and wage labourers in 17th-century Sweden, comparable to the labouring poor of other European countries.